PENGARUH VARIETAS DAN PELEMBABAN PADA VIABILITAS BENIH KEDELAI (Glycinemax[L.] Merrill) PASCASIMPAN TUJUH BELAS BULAN - Khoirul Akbar Sopian (Balitbangda Provinsi Lampung, 2021)
The objectives of this study were (1) to determine differences in seed viability of three soybean varieties (Anjasmoro, Grobogan, and Burangrang) after seventeen months of storage, (2) to determine differences in seed viability between moistened seed for 12 hours and unmoisturized seed, and (3) to determine differences in seed viability between moistened and unmoisturized seed in each variety. This research was conducted at the Seed Technology and Plant Breeding Laboratory, Faculty of Agriculture, University of Lampung from April to May 2019.This research was set in Randomized Block Design (RBD) that consist of three replication. The treatment design consisted of two factors that was arranged in a factorial (3x2). The first factor is soybean varieties which consist of three varieties (Anjasmoro (V1), Grobogan (V2), and Burangrang (V3)). The second factor was moistened seed for 0 hours (I0) and 12 hours (I1). The data homogeneity was tested by using the Bartlett test and the data additivity was tested by using the Tukey test. If the assumption is fulfilled, then the separation of the mean value was carried out by using orthogonal contrast at 5% significance level. The results showed that (1) the Burangrang variety had higher viability than the Grobogan variety after being stored for 17 months. This was based on the variable speed of germination and the vigor index of the Burangrang variety, namely 32.94% per etmal and 0.82; higher than the Grobogan variety, namely 29.67% per etmal and 0.76. (2) Moisturization for 12 hours resulted a germination rate of 34.01% per etmal and a vigor index of 0.84; higher than unmoisturized seed, which was 28.60% per etmal and 0.77. (3) The viability of moistened and unmoistened seed in each variety did not differ